PENERAPAN MODEL PROBLEM POSING LEARNING UNTUK MENIGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI KERAGAMAN SUKU BANGSA DAN BUDAYA DI INDONESIA (Penelitian Tindakan Kelas Pada Siswa Kelas V SDN Padarek III Kecamatan Lemahsugih Kabupaten Majalengka) - Pebriana, Yosi; Kurnia, Dadang; Panjaitan, Regina Lichteria (Jurnal Pena Ilmiah, 2017)
This was guided by the lack of critical thinking of SDN padarek III student at subject material tribes and cultures diversity of Indonesia. It was caused by teacher-centered learning method that make students less actively in achieving advance level of thinking. To oslve such problems, we used problem posing learning method then hopely will increase critical thinking of the students. This research used classroom action research model from Kemmis Taggart wich there were some circles, in every circle has plan, action, observation, and reflection. With conducting problem posing learning method which have proven success in increasing critical thinking of students. At cycle I critical thinking of students achieve 24% while at cycle II achieve 83%. Therefore, when teacher used problem posing learning method at material subject tribes and culture diversity significantly increased critical thinking of students of SDN Padarek III.